Creative activities for young children - Mayesky, Mary (New York : Delmar, 2002)
Contenido: Fostering creativity and aesthetics in young children. The concept of creativity. Promoting creativity. The concept of aesthetics. Promoting aesthetic experiences. Planning and implementing creative activities. Art and the development of the young child. The early childhood art program. Play, development, and creativity. Theory into practice: creative activities for the early childhood program. Creative activities in other curricular areas. Creative celebrations: holidays in the early childhood curriculum.